Digital Game Culture in Korea: The Social at Play - Chee, Florence M. (Lexington Books, 2023)
Digital Game Culture in Korea: The Social at Play is a critical ethnographic investigation of media discourses surrounding online game addiction and the sociocultural roles fulfilled by games in everyday life. Florence M. Chee argues that the casting of online games as singularly problematic or addictive largely ignores the socially generative and, at times, pivotally important means of connection among games, players, and the communities they foster. Through focusing on Korea’s sociohistorical and technocultural context, this work celebrates and recognizes the foundational role of Korean game culture in shaping global games and play. Scholars of game studies, communication, and technoculture will find this book of particular interest.